Filsafat Jawa: Belajar Menjadi Pemimpin dalam Ajaran Serat Tajusalatin - Setyo Pambudi; Rz. Ricky Satria Wiranata (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2020)
This research is a study of leadership values in the Tajusalatin that developed during the Surakarta and Yogyakarta palaces. Tajusalatin is growing very rapidly and contains moral teachings that can be a reference in today. One of the contents in the Tajusalatin is an example of a leader in work and social relations. The study of leadership values in this literary work can be called a Javanese-Islamic leadership model. This research is qualitative, this type of research is literature study. This research makes classical archives and literature as the basic foundation and the main tool in searching scientific facts. This research focuses on the forms of educational values and moral philosophy of leadership in the perspective of the Tajusalatin.